"See the Glory of my God Smaragdos": The Calf-Cult in the Martyrdom of Philotheos of Antioch and the Historical Background of the Golden Necklace (Torc) in Coptic Martyrdoms - Krueger, Frederic (Journal of Coptic studies, 2024)
This article examines the Biblical and hagiographical sources behind the cult of the sacred calf in the Martyrdom of Philotheos of Antioch, whose authentic connections to ancient Egyptian religion have been overestimated by previous scholarship. Special attention is furthermore paid to the historical context of the golden necklaces and bracelets that appear in many hagiographical works, mainly martyrdoms. These mostly reflect their use as soldiers' decoration in the late Roman army but also as elite fashion statements. In a further step, our text even uses them as the decadent cultic adornment in a pagan cult.